The mechanosensitive Piezo1 channel mediates heart mechano-chemo transduction - Fan Jiang (Nature Portfolio, 2021)
The beating heart adapts cardiac output to changes in mechanical load via incompletely understood mechanotransduction mechanisms. Here the authors show that the mechanosensitive Piezo1 channel serves as a mechanotransducer for directly converting mechanical stretch of cardiomyocytes into Ca2+ and ROS signaling and consequently maintaining normal heart function.